Altruism - as a National Value for Uzbek People - Nishanova, Zamira Taskarevna; Atabaeva, Nargis Batirovna; Khalmuratova, Dilaram Abdikarimovna; Djolimbetova, Miywagul Madiyarovna (International Journal of Psychosocial Rehabilitation, 2020)
The article analyzes the importance of altruistic behavioral motives in the formation of national characteristics of the Uzbek people and the psychological features of the manifestation of altruism as a national value. Altruism is a trait that manifests itself in a behavioral motive that defines our level of spiritual maturity, encouraging us to help the people around us, not to be indifferent to the problems of our loved ones and society. The phenomenon of altruism, which is one of the features of the Uzbek national mentality, is described in the sacred sources and in the works of Eastern scholars on the basis of the science of futuwwat, which is similar to it in the interpretation of such qualities as goodness, generosity, kindness, impartial assistance. In addition, the essence of moral, cognitive, social, psychological factors influencing the harmonization of behavior based on altruistic motives with the system of personal values in the research of foreign psychologists is systematized taking into account ethnic characteristics. The article analyzes the correlation between altruism and the manifestation of national characteristics during adolescence on an empirical basis, taking into account age and gender aspects. On the basis of analytical data, scientific conclusions were formed and pedagogical-psychological recommendations were developed for pedagogical psychologists and parents for the development of altruism in adolescents as a national feature and value.